Au-loaded TiO2 and Ag-loaded TiO2 synthesized by modified sol-gel/impregnation method as photocatalysts - Ninsonti H. (2017)
© 2016 The Japan Society of Applied Physics. In this work, Au-loaded TiO 2 and Ag-loaded TiO 2 nanoparticles were synthesized by modified sol-gel method together with impregnation method. The samples were characterized by their physicochemical properties using X-ray diffraction (XRD) and X-ray photoelectron spectroscopy in order to obtain the correlation between structure and photocatalytic properties. XRD results indicated unloaded TiO 2 , Au-loaded TiO 2 and Ag-loaded TiO 2 nanoparticles were all in the anatase phase with average crystallite size in the range of 10-13 nm. In addition, XPS analysis confirmed the presence of Au and Ag elements in Au-loaded TiO 2 and Ag-loaded TiO 2 nanoparticles, respectively. The photocatalytic activities of TiO 2 , Au-loaded TiO 2 and Ag-loaded TiO 2 nanoparticles were evaluated through the mineralization of formic acid under UV-light illumination. The results showed that Au-loading and Ag-loading could effectively improve the photocatalytic activities of TiO 2 . Furthermore, Au-loaded TiO 2 exhibited a higher photocatalytic activity than Ag-loaded TiO 2 .